Effectiveness of Action Observation Training on Upper Limb Motor Function in Children with Hemiplegic Cerebral Palsy: A Systematic Review of Randomized Controlled Trials - Alamer A; Melese H; Adugna B (Dove Medical Press, 2020)
Abayneh Alamer,1 Haimanot Melese,1 Belaynew Adugna2 1Department of Physiotherapy, School of Medicine, College of Health Sciences, Ayder Comprehensive Specialized Hospital, Mekelle University, Mekelle, Ethiopia; 2Department of Physiotherapy, School of Medicine, College of Health Sciences, Tibebe Ghion Comprehensive Specialized Hospital, Bahirdar University, Bahirdar, EthiopiaCorrespondence: Haimanot Melese Tel +251 927608383Fax +251 344416681Email haimanotphysio@gmail.comAbstract: The purpose of this review was to evaluate and examine the current best evidence for the effectiveness of action observation therapy on upper limb function rehabilitation in children with hemiplegic cerebral palsy. A comprehensive search of literature published between September 2010 and May 2020 was conducted using the following electronic databases: PubMed, Google Scholar, the Physiotherapy Evidence Database (PEDro), EMBASE, Cochrane library, and Scopus. Only randomized controlled trials evaluating the effect of action observation therapy on upper limb motor function in children with hemiplegic cerebral palsy were included. PEDro scale was used to assess the risk of bias of included trials. This study was reported according to the guideline of the PRISMA statement. The overall methodological quality of the studies was done using the PEDro scale and GRADE approach. The primary outcome measures of this review were the Melbourne Assessment Scale, Assisting Hand Assessment scale to evaluate physical function and structures. Furthermore, the ABILHAND-Kids test, and Box and Block Test primary outcome measures were used to determine the subjects’ activities and participation. Nine randomized controlled trials involving 234 participants were analyzed. The overall quality of evidence was rated from moderate to high. This review suggests action observation therapy was found to be a promising intervention for upper limb rehabilitation in children with cerebral palsy.Keywords: action observation training, hemiplegic CP, upper extremity motor function, systematic review